NARASI KEMATIAN DALAM FIKSI INDONESIA MODERN: PERSPEKTIF PSIKOLOGI KEMATIAN - Ahmadi, Anas (Pusat Pengembangan Bahasa IAIN Tulungagung, 2019)
This study aims to explore the narrative of death in the Indonesian fiction short story genre. The narrative of death appears in two segments, namely (1) death type narratives in Indonesian fiction and (2) post-death narratives in Indonesian fiction. The method used is qualitative with the description of data using Indonesian short story data sources collected in the Kasur Tanah: Cerpen Pilihan Kompas 2017 (2018). The results showed that the death narrative in Indonesian fiction appeared and represented in segmentation (1) the type of death that was natural (short story